Persepsi Petani Terhadap Model Replanting Tumbang Serempak Pada Tanaman Kelapa Sawit - zakiah zakiah; Ilmi Nur Naini; Arsyad Lubis; Endy Efran; Siti Kurniasih (Universitas Batangahari Jambi, 2023)
The age of the oil palm plants in Sungai Bulian Village is currently 30 years old, so the productivity of the oil palm plants in Sungai Bulian Village has decreased. It's time for farmers to do replanting. One of the replanting models that can be applied is the simultaneous fall model. The purpose of this study was to determine farmers' perceptions of the replanting model of the simultaneous fall of oil palm plants in Sungai Bulian Village, East Tabir District, Merangin Regency, and to determine the tendency of farmers to choose the oil palm replanting model which was socialized to farmers in Sungai Bulian Village, East Tabir District, Regency. Merangin, as well as analyzing the relationship between perceptions and the tendency of farmers to choose the model of replanting the fallen oil palm plants simultaneously which was socialized to farmers in Sungai Bulian Village, Tabir Timur District, Merangin Regency. Determination of the sample in this study was determined by using a purposive sampling technique, the number of samples used as respondents in this study were 83 farmers. Data analysis in this study used quantitative descriptive analysis. Based on the results of the study, it was shown that farmers' perceptions of the replanting model of simultan fall and oil palm plants in Sungai Bulian Village, Tabir Timur District, Merangin Regency were in the high (good) category. The tendency of farmers in choosing the oil palm model that was socialized to farmers in Sungai Bulian Village, Tabir Timur District, Merangin Regency was to choose the model that fell simultaneously as much as 43.37%. Furthermore, farmers' perceptions are related to the tendency of farmers to choose the model of replanting fallen and oil palm plants which were socialized to farmers in Sungai Bulian Village, Tabir Timur District, Merangin Regency.